A layered bismuth nanoflower modified silk screen printed electrode and a preparation method and application thereof

CN122879776APending Publication Date: 2026-10-09UNIV OF SHANGHAI FOR SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610913084.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0009]本发明的目的就是为了解决现有重金属检测方法中存在的分布不均匀、结构致密性差、有效面积小导致的传感器灵敏度不足的问题而提供一种层状铋纳米花(LayeredBismuth Nanoflowers,L-BiNFs)修饰的丝网印刷电极(SPE)及其制备方法与应用,所述电极修饰材料为层状铋纳米花,所述层状铋纳米花由铋元素组成,该层状铋纳米花具有由纳米单元堆叠而成的二维层状分级纳米花结构

Benefits of technology

a.本发明所制备的丝网印刷电极制备方法简单,采用计时电流法在丝网印刷电极上直接沉积L-BiNFs,无需复杂后处理,避免了抛光预处理步骤。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879776A_ABST
    Figure CN122879776A_ABST
Patent Text Reader

Abstract

The application relates to a layered bismuth nanoflower modified silk screen printing electrode and a preparation method and application thereof. The electrode modification material is a layered bismuth nanoflower which is composed of bismuth elements and has a two-dimensional hierarchical nanoflower structure formed by layer-by-layer stacking of nanometer units. The preparation method of the silk screen printing electrode is as follows: in an electrodeposition solution containing ethylenediaminetetraacetic acid and bismuth ions, layered bismuth nanoflowers are in-situ grown on the surface of the silk screen printing electrode through chronocoulometry. An electrochemical sensor constructed by taking the silk screen printing electrode as a working electrode can simultaneously detect cadmium ions and lead ions in water by using a square wave anodic stripping voltammetry method. Compared with the prior art, the layered bismuth nanoflower structure is uniform, has good conductivity, and has a large effective active area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical sensor technology, and in particular to a screen-printed electrode modified with layered bismuth nanoflowers, its preparation method, and its application. Background Technology

[0002] With the significant increase in discharges from industrial wastewater, agricultural runoff, and other human activities, heavy metal pollution in water bodies is becoming increasingly serious. Cadmium (Cd) and lead (Pb), as two typical toxic heavy metals, can cause serious damage to the kidneys, liver, nervous system, and bones even with long-term exposure at trace levels. The World Health Organization (WHO) has set a high standard for cadmium ions (Cd) in drinking water. 2+ ) and lead ions (Pb 2+ Strict limits have been set for the concentration of Cd. 2+ Not exceeding 5 μg / L, Pb 2+ (Not exceeding 10 μg / L). Therefore, developing a rapid, reliable, and field-appropriate method for the simultaneous determination of these two metal ions has become an urgent need in the field of environmental monitoring.

[0003] Currently, the main technologies for detecting heavy metal ions include spectroscopic methods (such as atomic absorption spectrometry and inductively coupled plasma mass spectrometry) and chromatographic methods (such as high-performance liquid chromatography and ion chromatography). These methods are highly sensitive and accurate, but the instruments are expensive, the operation is complex, and the sample pretreatment is cumbersome, making them unsuitable for on-site screening applications. Electrochemical detection methods are low-cost, easy to operate, highly sensitive, and the equipment is portable. In particular, the square wave anodic stripping voltammetry combines a simple pre-enrichment step with rapid potential scanning, enabling the simultaneous detection of multiple metal ions with detection limits down to the ppb level, making it ideal for on-site water quality assessment.

[0004] For decades, mercury-based electrodes have been classic detection electrodes for leaching analysis due to their ability to form amalgams with various heavy metals and their wide cathode potential window. However, the high toxicity of mercury has prompted researchers to seek environmentally friendly alternatives. Bismuth, with its ability to form alloys with target metals and produce clear leaching peaks, has become one of the most promising alternatives. Currently, methods for modifying electrodes with bismuth mainly include precursor reduction, in-situ electrodeposition, and ex-situ electrodeposition. Among these, ex-situ electrodeposition is simple to operate and offers good controllability. However, bismuth films prepared by existing methods often suffer from uneven distribution, poor structural density, and small effective area, limiting the sensitivity of the sensors.

[0005] Screen-printed electrodes (SPEs) integrate the working electrode, reference electrode, and counter electrode onto a PVC or polyester substrate. They offer significant advantages such as low cost, mass production capability, and single-use without the need for polishing pretreatment, making them more suitable for building portable, disposable field detection sensors.

[0006] Chinese patent CN115182012A discloses a method for preparing a bismuth nanoflower-modified electrode and its sensing application. The bismuth nanoflowers are nanoscale bismuth elements with a flower-like morphology, composed of plate-like bismuth crystals as structural units. The preparation method includes the following steps: preparing an acidic electroplating solution containing stannous salt and bismuth salt; immersing the electrode in the electroplating solution; electroplating using a constant potential method between the bismuth reduction potential and the tin reduction potential; rinsing and drying; and placing the electrode in a sealed bag. The preparation process of the bismuth nanoflower-modified electrode described in this application is simple, with strong tunability of the microstructure, and it can be used to detect heavy metal ions in aqueous solutions, exhibiting high detection sensitivity and stability. However, the three-dimensional structure of bismuth nanoflowers composed of plate-like bismuth crystals has weak interlayer bonding, making them prone to structural collapse and detachment under long-term continuous detection or complex aquatic environments, leading to attenuation of the electrode response signal and affecting detection performance.

[0007] Chinese patent CN115504544A discloses a method for preparing a Cu-Bi / TiO2 nano-electrocatalytic denitrification electrode. The method involves electrodepositing copper-bismuth metal onto the surface of a titanium dioxide nanoelectrode to obtain a Cu-Bi / TiO2 nanoelectrode, and describes its use for electrocatalytic reduction of nitrate nitrogen in water. The Cu-Bi / TiO2 nano-electrocatalytic electrode prepared in this application exhibits high reactivity and removal efficiency for nitrate nitrogen in water, showing great application potential. However, Cu metal exhibits strong hydrogen evolution competition during nitrate reduction, with the main reduction product being ammonia nitrogen rather than harmless nitrogen gas. Although the introduction of Bi can improve nitrogen selectivity to some extent, a considerable proportion of nitrogen-containing intermediates still remain in the water, posing a risk of secondary pollution.

[0008] In summary, developing a high-performance bismuth-modified electrode based on SPE is of great significance for improving the electrochemical detection performance of heavy metal ions. Summary of the Invention

[0009] The purpose of this invention is to address the problems of insufficient sensor sensitivity caused by uneven distribution, poor structural density, and small effective area in existing heavy metal detection methods. This invention provides a screen-printed electrode (SPE) modified with layered bismuth nanoflowers (L-BiNFs), its preparation method, and its application. The electrode modification material is layered bismuth nanoflowers, which are composed of bismuth elements and have a two-dimensional layered hierarchical nanoflower structure formed by stacked nanounits.

[0010] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing a screen-printed electrode modified with layered bismuth nanoflowers, comprising the following steps: a. Preparation of electrodeposition solution: Dissolve bismuth salt and complexing agent in ultrapure water and adjust pH to obtain electrodeposition solution; b. Immerse the electrode in the electrodeposition solution obtained in step a, and perform electrodeposition using a chronoamperometry to obtain a layered bismuth nanoflower modified electrode; c. Take out the layered bismuth nanoflower modified electrode obtained in step b, wash it with ultrapure water, and dry it to obtain the screen-printed electrode modified with layered bismuth nanoflower.

[0011] Furthermore, in step a, the bismuth salt is bismuth nitrate pentahydrate.

[0012] Further, in step a, the complexing agent is ethylenediaminetetraacetic acid, wherein the molar ratio of bismuth salt to complexing agent is 1:1.5-2.5.

[0013] Further, in step a, the pH is adjusted to 3.0-4.0 by using NaOH and HCl or HNO3.

[0014] Furthermore, in step b, the electrodeposition potential is -1.1 V to -0.7 V; the deposition time is 60 to 420 s; and the stirring speed during the deposition process is 200 to 300 rpm.

[0015] In a second aspect, the present invention provides a screen-printed electrode modified with layered bismuth nanoflowers, which is obtained by any of the preparation methods described above. The layered bismuth nanoflowers are composed of bismuth elements and have a two-dimensional hierarchical nanoflower structure formed by stacking layers of nanounits.

[0016] In a third aspect, the present invention provides the application of a screen-printed electrode modified with layered bismuth nanoflowers in an electrochemical sensor.

[0017] Furthermore, the electrochemical sensor also includes a working electrode, a reference electrode, and a counter electrode. The working electrode is a layered bismuth nanoflower composite electrode; the reference electrode is Ag / AgCl; and the counter electrode is a graphite-carbon black composite conductive carbon electrode. The working electrode, reference electrode, and counter electrode are integrated on the same screen-printed electrode substrate.

[0018] Furthermore, the electrochemical sensor was applied to the square-wave anodic stripping voltammetry method for the detection of Cd in water samples. 2+ and Pb 2+ This includes the following steps: a. Mix the water sample to be tested with the buffer solution and adjust the pH; b. Stirring at the enrichment potential; c. Square wave anodic stripping voltammetry was used to scan and record the stripping peak currents of cadmium and lead ions; d. Calculate Cd based on the dissolution peak currents of cadmium and lead ions obtained in step c. 2+ and Pb 2+ The concentration.

[0019] Further, in step a, the buffer solution is an acetic acid and sodium acetate buffer solution with a concentration of 0.01-0.2 mol / L, and the pH is adjusted to 3.5-5.5 by adding acetic acid and anhydrous sodium acetate. In step b, Pb 2+ The enrichment potential is -1.7 V to -1.1 V; Cd 2+ The enrichment potential ranges from -1.5 V to -1.1 V; the enrichment time ranges from 60 to 420 s. In step c, the potential step of the square wave anodic stripping voltammetry is 3-5 mV, the square wave amplitude is 20-30 Hz, and the frequency is 10-20 Hz.

[0020] Compared with the prior art, the present invention has the following beneficial effects: a. The screen-printed electrode preparation method of the present invention is simple. L-BiNFs are directly deposited on the screen-printed electrode using the chronoamperometry method, without the need for complex post-processing and avoiding the polishing pretreatment step.

[0021] b. The L-BiNFs prepared in this invention have a two-dimensional hierarchical structure and a large effective electroactive area, which can effectively improve the resistance to Cd. 2+ and Pb 2+ The enrichment efficiency and detection sensitivity of Cd. Simultaneous detection of Cd 2+ and Pb 2+ The detection limits were 2.47 μg / L and 1.01 μg / L, respectively, meeting the World Health Organization's limits for harmful metal ions in drinking water.

[0022] c. The sensor using the screen-printed electrode prepared according to the present invention exhibits good anti-interference capability at a concentration of 100 times K. + Na + NH4 + Zn 2+ Fe 3+ Mg 2+ In the presence of coexisting ions, Cd 2+ and Pb 2+ The peak currents all remained above 90% of their original values.

[0023] d. The entire system of the present invention can be integrated onto a portable screen-printed electrode, facilitating miniaturization and on-site testing applications.

[0024] In summary, the L-BiNFs / SPE electrode preparation method of this invention is simple, low-cost, and environmentally friendly, exhibiting high electrochemical activity and capable of achieving Cd… 2+ and Pb 2+ Rapid simultaneous detection, with detection ranges of 10–50 μg / L (Cd 2+ ) and 5~50 μg / L (Pb 2+ It has a low detection limit and good anti-interference ability, and is expected to be applied to the on-site portable detection of actual water samples in the future. Attached Figure Description

[0025] Figure 1 (a) SEM image of the unprocessed SPE surface; Figure 1 (b) Figure 1 (c) is a SEM image of the L-BiNFs / SPE surface; Figure 2 The images are EDS mapping diagrams and spectra obtained by EDS testing of the L-BiNFs / SPE prepared in Example 1 of this invention; wherein... Figure 2 (a) is a scanning electron microscope image of bismuth nanoflowers; Figure 2 (b) is the EDS surface distribution diagram of the Bi element in the corresponding region; Figure 2 (c) is the full EDS energy spectrum of L-BiNFs / SPE; Figure 3 (a) Untreated SPE and L-BiNFs / SPE prepared in Example 1 at a scan rate of 50 mV·s -1 Cyclic voltammetry at scan rate; Figure (b) shows the electrochemical impedance spectroscopy spectra obtained from untreated SPE and L-BiNFs / SPE. Figure 4 It contains Cd at a concentration of 50 μg / L 2+ and Pb 2+ A schematic diagram comparing the detection results of untreated SPE and L-BiNFs / SPE using square wave anodic stripping voltammetry in electrolyte solutions under unoptimized conditions. Figure 5 The current obtained using square wave anodic stripping voltammetry in Examples 2-6 is related to (bismuth film deposition time, bismuth film deposition potential, Cd). 2+ and Pb 2+ Figures showing enrichment potential, enrichment time, and electrolyte solution pH; where Figures (a)-(e) correspond to Examples 2-6, respectively. Figure 6 The prepared L-BiNFs / SPE is effective against different concentrations of Cd. 2+ and Pb 2+Simultaneous detection of standard curves; Figure 7 This is an analysis diagram of the anti-interference capability of L-BiNFs / SPE. Detailed Implementation

[0026] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0027] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, although not explicitly stated, each point or individual value between the endpoints of a range is included within that range. Therefore, each point or individual value can be used as its own lower or upper limit and combined with any other point or individual value, or combined with other lower or upper limits, to form a range not explicitly stated. In the description of this application, it should be noted that, unless otherwise stated, "above" includes the stated number, and "multiple" in "one or more" means two or more.

[0028] The foregoing description of this application is not intended to describe every disclosed implementation or method. Instead, the following description provides more specific examples of exemplary embodiments. Throughout the application, guidance is provided through a series of embodiments that can be used in various combinations. The examples listed are representative only and should not be construed as exhaustive.

[0029] Numerous details are explored in the following description to provide a more thorough explanation of embodiments of this application; however, it will be apparent to those skilled in the art that embodiments of this application may be practiced without these specific details.

[0030] The key technical problem that this invention needs to solve is: (1) Electrode modification materials This invention provides an electrode modification material for heavy metal ion detection. The material is a layered bismuth nanoflower, composed of bismuth and possessing a two-dimensional hierarchical nanoflower structure formed by stacked layers of nanounits. Specifically, this structure consists of a large number of tiny nanounits arranged tightly in a "layered building block" manner, with abundant voids and channels between the units.

[0031] The layered bismuth nanoflowers are formed in situ on the surface of a screen-printed electrode using a chronoamperometry method. The advantage of in-situ formation is that the modified layer and the electrode substrate are tightly bonded, eliminating the need for additional adhesives and avoiding the obstruction of electron transport by adhesives.

[0032] The electrodeposition solution used in the chronoamperometry method is a mixed solution containing ethylenediaminetetraacetic acid (EDTA) and bismuth nitrate pentahydrate (Bi(NO3)3·5H2O). EDTA acts as a chelating agent, and its carboxylate functional group can react with bismuth ions (Bi... 3+ Coordination occurs, forming Bi 3+ -EDTA complex. This complex can significantly improve Bi... 3+ The stability during the electrodeposition process promotes the formation of uniform, dense layered nanoflower structures.

[0033] (2) Setting the preparation conditions for the modified electrode In this invention, when bismuth nanostructures are prepared on the surface of screen-printed electrodes using the chronoamperometry method, the deposition potential and deposition time directly affect the morphology, thickness, and electrochemical activity of the bismuth nanoflowers.

[0034] a. Deposition potential: When the deposition potential is too positive, it affects Bi... 3+ Insufficient reduction driving force leads to an excessively thin modified layer; when the deposition potential is too negative, the deposition morphology deteriorates and the bismuth film distribution is uneven.

[0035] b. Insufficient deposition time results in fewer active sites on the electrode surface; excessive deposition time leads to an overly thick bismuth layer that hinders electron transfer. Therefore, it is necessary to optimize the deposition potential and deposition time to obtain uniform layered bismuth nanofloriformes. (3) Setting of multiple parameters during the detection process Detection of Cd by Square Wave Anodic Stripping Voltammetry 2+ and Pb 2+ At this time, the enrichment potential, enrichment time, and pH value of the supporting electrolyte have a significant impact on the detection sensitivity.

[0036] a. Enrichment potential: When the enrichment potential is too positive, the driving force for the reduction of metal ions weakens and the enrichment efficiency decreases; when the enrichment potential is too negative, the hydrogen evolution reaction will interfere with the enrichment.

[0037] b. Enrichment time: If the enrichment time is too short, heavy metal ions cannot be fully enriched; if the enrichment time is too long, excessive enrichment on the electrode surface will hinder electron transfer.

[0038] c. Electrolyte solution pH: If the pH of the supporting electrolyte is too low, the hydrogen evolution reaction will produce bubbles that destroy the modified layer; if the pH is too high, Cd... 2+ and Pb 2+ It will hydrolyze to form hydroxide precipitates. Therefore, these parameters need to be optimized.

[0039] To further understand this invention, the following embodiments are provided. It is worth noting that, unless otherwise specified, all raw materials used in this invention are commercially available; and all methods and equipment used are common in the art. Specifically, the untreated SPE electrode was purchased from Changsha Sanjun Electronic Technology Co., Ltd., China; the electrochemical workstation used for electrochemical testing was a CHI660E (Shanghai Chenhua Instrument Co., Ltd.), and the SEM instrument was an Apreo 2 (ThermoFisher Scientific, USA).

[0040] The predetermined standard curve in the embodiment is determined through the following steps: such as Figure 6 As shown, within the concentration range of 10-50 µg / L, the current value varies with Cd. 2+ The concentration increases and continues to rise, Cd 2+ The dissolution peak current exhibits a good linear relationship with its concentration, and the fitted calibration curve equation is I. Cd = (0.2474±0.0034)C-(1.5645±0.0611), R 2 It is 0.9993. Also within the range of 5-50 µg / L, Pb... 2+ The dissolution peak current also increases linearly with increasing concentration, and the fitted calibration curve equation is I. Pb = (0.2873±0.0074)C-(0.8582±0.0858), R 2 The value is 0.9967. Cd can be calculated from the measured current value. 2+ and Pb 2+ The concentration.

[0041] Example 1 This embodiment provides a method for preparing a screen-printed electrode L-BiNFs / SPE modified with layered bismuth nanoflowers, including the following steps: a. Preparation of electrodeposition solution: First, add 0.1461 g of EDTA to an ultrapure aqueous solution, adjust the pH to 5.0 with NaOH and HCl, and then add 0.1212 g of Bi(NO3)3·5H2O to obtain 50 ml of electrodeposition solution.

[0042] b. Preparation of layered bismuth nanoflower modified electrode: Chorothermal electrodeposition was performed using a constant potential method. The untreated screen-printed electrode was directly immersed in 10 ml of the electrodeposition solution obtained in step a), and deposition was carried out at -0.8 V (Ag / AgCl as the reference electrode) for 240 s. During deposition, stirring was maintained at 200 rpm to promote ion diffusion and uniform deposition of the bismuth nanostructures. After deposition, the modified electrode was gently rinsed with ultrapure water to remove loosely adsorbed Bii from the surface. 3+ The modified electrode is L-BiNFs / SPE, which is obtained by deriving an EDTA complex and then air-drying it at room temperature.

[0043] c. Using the L-BiNFs / SPE obtained in step b as the working electrode, Ag / AgCl as the reference electrode, and graphite-carbon black composite conductive carbon as the counter electrode, and a 0.1 mol / L acetate-sodium acetate buffer solution at pH 4.5 as the electrolyte solution, Cd was detected by square wave anodic stripping voltammetry. 2+ and Pb 2+ After enrichment and dissolution steps, the dissolution peak currents of cadmium and lead ions were recorded. The enrichment stage was carried out with stirring at 200 rpm, the enrichment potential was -1.3 V (for simultaneous detection), and the enrichment time was 300 s. The dissolution stage parameters were: potential step 4 mV, square wave amplitude 25 mV, and frequency 15 Hz. After collecting the dissolution peak current data of cadmium and lead ions, the simultaneous detection of Cd by L-BiNFs / SPE was calculated using a predetermined standard curve. 2+ and Pb 2+ The limits of detection (LODs) were 2.47 μg / L and 1.01 μg / L, respectively. Both limits of detection meet the World Health Organization's requirements for Cd in drinking water. 2+ (not exceeding 5 μg / L) and Pb 2+ (Not exceeding 10 μg / L) limit requirements.

[0044] Example 2 This embodiment is largely the same as Embodiment 1, except that the electrodeposition time in step b is gradually increased from 60 s to 360 s. Otherwise, it is the same as Embodiment 1.

[0045] Example 3 This embodiment is largely the same as Embodiment 1, except that the electrodeposition potential in step b is gradually adjusted from -1.1V to -0.7V. Otherwise, it is the same as Embodiment 1.

[0046] Example 4 This embodiment is largely the same as Embodiment 1, except that Pb in step b is changed. 2+The enrichment potential was gradually adjusted from -1.7 V to -1.1 V; Cd 2+ The enrichment potential was gradually adjusted from -1.5 V to -1.1 V, and the rest was the same as in Example 1.

[0047] Example 5 This embodiment is largely the same as Embodiment 1, except that the enrichment time in step c is gradually adjusted from 60s to 420s. Otherwise, it is the same as Embodiment 1.

[0048] Example 6 This embodiment is largely the same as Example 1, except that the pH of the buffer solution in step c is gradually adjusted from 3.5 to 5.5. Otherwise, it is the same as Example 1.

[0049] Performance testing 1. Morphological testing The untreated SPE and the L-BiNFs / SPE prepared in Example 1 were characterized by SEM, and the results are as follows: Figure 1 As shown. Figure 1 a shows the surface morphology of SPE, which is formed by the accumulation of carbon particles with voids of varying sizes between the particles, and the surface is generally rough. Figure 1 (b) Figure 1 (c) Shows the surface morphology of L-BiNFs / SPE at different magnifications; from Figure 1 (b) shows that nanoscale layered materials appear on the electrode surface, exhibiting a hierarchical nanoflower morphology resembling stacked building blocks, with a dense overall structure; from Figure 1 As can be seen in (c), these hierarchical nanoflowers are composed of a large number of tiny nanounits stacked layer by layer, forming a unique two-dimensional hierarchical structure.

[0050] 2. EDS Analysis Figure 2 The image shows the EDS mapping and spectrum obtained by EDS testing of the L-BiNFs / SPE prepared in Example 1 of this invention. Figure 2 (a) Figure 2 (b) is the EDS mapping diagram, from Figure 2 (a) shows that the sample exhibits a uniform flower-like hierarchical structure; from Figure 2 (b) shows that the orange signal completely overlaps with the SEM morphology, indicating that bismuth is uniformly distributed in the flower-like structure; Figure 2 (c) is a spectrum of the total number of bismuth elements. It can be seen from the figure that the modified layer is composed of Bi elements and no other impurity elements were detected.

[0051] 3. Electrochemical characterization The electrochemical activity and conductivity of untreated SPE and L-BiNFs / SPE were evaluated using cyclic voltammetry and electrochemical impedance spectroscopy. The test solution was a 10 mmol / L K3[Fe(CN)6] solution containing 1 mol / L KCl.

[0052] Cyclic Voltmeter Test Results Figure 3 As shown in the figure, at 50 mV·s -1 At the specified scan rate, the oxidation peak current of untreated SPE was 91.02 μA, the reduction peak current was 98.31 μA, and the peak potential difference was 310 mV. The oxidation-reduction currents of L-BiNFs / SPE were 107.75 μA and 113.88 μA, respectively, with a significant increase in oxidation-reduction peak current and a decrease in peak potential difference to 250 mV. This indicates that L-BiNFs is an effective electrode modification material. It successfully improved the electrochemical performance of SPE, specifically by significantly enhancing the response current (beneficial for high-sensitivity detection) and reducing the peak potential difference (beneficial for improving reaction reversibility and selectivity).

[0053] Electrochemical impedance spectroscopy test results Figure 3 As shown in Figure b, the charge transfer resistance of the untreated SPE is 2522 Ω, while that of the L-BiNFs / SPE is 952 Ω, indicating that the L-BiNFs / SPE has better conductivity and electron transfer capability.

[0054] 4. L-BiNFs / SPE on Cd 2+ and Pb 2+ Detection performance Figure 4 To determine the optimal detection method under unoptimized experimental conditions in a solution containing 50 μg / L Cd. 2+ and Pb 2+ A schematic diagram comparing the detection results of untreated SPE and L-BiNFs / SPE in electrolyte solutions using square wave anodic stripping voltammetry. From... Figure 4 As can be seen, the untreated SPE produces Cd at -0.978 V and -0.672 V. 2+ and Pb 2+ The dissolution peaks were observed, with peak currents of 0.52 μA and 3.15 μA, respectively, while L-BiNFs / SPE produced Cd at -0.996 V and -0.780 V. 2+ and Pb 2+ The dissolution peaks were observed, with peak currents of 4.01 μA and 12.32 μA, respectively. This demonstrates that the L-BiNFs membrane possesses good electrocatalytic ability and electrochemical activity, which is beneficial for the enrichment of heavy metal ions.

[0055] 5. Optimization of testing conditions To obtain optimal detection performance, deposition potential and deposition time were monitored during the processes of Examples 2-6, and the data are as follows: Figure 5 As shown in (ae).

[0056] from Figure 5 As can be seen in (a), the deposition time ranges from 60 s to 360 s, and the Cd... 2+ and Pb 2+ The dissolution peak current gradually increased from 2.84 μA and 5.25 μA; it reached its maximum value of 7.33 μA and 12.67 μA at 240 s; the peak current decreased after 240 s. Therefore, the optimal deposition time is 240 s.

[0057] from Figure 5 As can be seen in (b), the deposition potential ranges from -1.1 V to -0.8 V, and the Cd... 2+ and Pb 2+ The dissolution peak current continuously increases, reaching its maximum value of 7.33 μA and 12.67 μA at -0.8 V; when the potential is further reduced to -0.7 V, the peak current drops sharply. Therefore, the optimal deposition potential is -0.8 V.

[0058] from Figure 5 (c) shows that for Cd 2+ The peak current is largest at the enrichment potential of -1.3 V, reaching 13.43 μA; for Pb 2+ The peak current, at 17.65 μA, was highest at an enrichment potential of -1.5 V. Potentials that were more negative or more positive resulted in decreased enrichment efficiency. To avoid increased background current and hydrogen evolution side reactions caused by excessively negative potentials during simultaneous detection, -1.3 V was selected as the common enrichment potential.

[0059] from Figure 5 As shown in (d), the peak current gradually increases from 60 s to 420 s; it reaches its maximum value of 13.43 μA and 17.65 μA at 300 s; after 300 s, the peak current slowly decreases. Therefore, the optimal enrichment time is 300 s.

[0060] from Figure 5 As shown in (e), the peak current gradually increases as the pH increases from 3.5 to 4.5; it reaches its maximum value of 13.43 μA and 17.65 μA at pH=4.5; the peak current decreases when the pH continues to increase to 5.5. Therefore, a 0.1 mol / L acetic acid and sodium acetate buffer solution at pH=4.5 is selected as the optimal electrolyte solution.

[0061] 6. Determination of the standard curve To achieve simultaneous and effective detection of the two ions, while avoiding interference from increased background current and hydrogen evolution side reactions that might result from excessively negative potentials, -1.3 V was selected as the common enrichment potential. Figure 6 As shown in (a), within the concentration range of 10-50 µg / L, the current value varies with Cd 2+ The concentration increases and continues to rise, Cd 2+ The dissolution peak current exhibits a good linear relationship with its concentration, and the fitted calibration curve equation is I. Cd = (0.2474±0.0034)C-(1.5645±0.0611), R 2 It is 0.9993. Also within the range of 5-50 µg / L, Pb... 2+ The dissolution peak current also increases linearly with increasing concentration, and the fitted calibration curve equation is I. Pb = (0.2873±0.0074)C-(0.8582±0.0858), R 2 It is 0.9967. Figure 6 (b) is a predetermined standard curve. Cd can be calculated by substituting the dissolution peak current into the ordinate. 2+ With Pb 2+ The concentration of L-BiNFs / SPE for simultaneous detection of Cd was calculated. 2+ and Pb 2+ The limits of detection (LODs) were 2.47 μg / L and 1.01 μg / L, respectively. Both limits of detection meet the World Health Organization's requirements for Cd in drinking water. 2+ (not exceeding 5 μg / L) and Pb 2+ (Not exceeding 10 μg / L) limit requirements.

[0062] 7. Anti-interference test In a concentration of 50 μg / L Cd 2+ and Pb 2+ Add 100 times the concentration of K to the solution respectively. + Na + NH4 + Zn 2+ Fe 3+ Mg 2+ Common coexisting ions were observed, and the changes in the test response current were recorded. The results are as follows: Figure 7 As shown. From Figure 7 As can be seen, compared with using untreated SPE, the electrochemical sensor prepared using the L-BiNFs / SPE prepared in Example 1 for measuring Cd... 2+ and Pb 2+The peak currents remained above 90% of their original values, indicating that the electrochemical sensor prepared using the L-BiNFs / SPE prepared in Example 1 effectively detects Cd. 2+ and Pb 2+ It has good selectivity.

[0063] In summary, this invention prepared an L-BiNFs modified layer on an untreated SPE surface via chronoamperometry electrodeposition. Based on the chelating effect of EDTA, the Bi... 3+ The uniform deposition of L-BiNFs formed a unique two-dimensional hierarchical nanoflower structure, which is conducive to the enrichment of heavy metal ions. The conductivity of L-BiNFs-modified cells was greatly improved (charge transfer resistance decreased from 2522 Ω to 952 Ω), which accelerated interfacial electron transfer and improved the sensitivity of the sensor. The constructed L-BiNFs / SPE electrochemical sensor was used to establish a method for the simultaneous detection of Cd in aqueous solution. 2+ and Pb 2+ The electrochemical method exhibits good linearity when both ions are detected simultaneously (Cd). 2+ At concentrations of 10–50 μg / L, Pb 2+ Within the range of 5–50 μg / L, under optimal experimental conditions, the limits of detection reached 2.47 μg / L and 1.01 μg / L, respectively, far below the limits recommended by the World Health Organization (WHO) for Cd in drinking water. 2+ Not exceeding 5 μg / L, Pb 2+ The concentration of heavy metal ions in water does not exceed 10 μg / L, and the sensor has strong anti-interference ability, indicating that the constructed sensing platform has great potential for detection of heavy metal ions in water.

[0064] The foregoing has shown and described the basic process, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a screen-printed electrode modified with layered bismuth nanoflowers, characterized in that, Includes the following steps: a. Preparation of electrodeposition solution: Dissolve bismuth salt and complexing agent in ultrapure water and adjust pH to obtain electrodeposition solution; b. Immerse the electrode in the electrodeposition solution obtained in step a, and perform electrodeposition using a chronoamperometry to obtain a layered bismuth nanoflower modified electrode; c. Take out the layered bismuth nanoflower modified electrode obtained in step b, wash it with ultrapure water, and dry it to obtain the screen-printed electrode modified with layered bismuth nanoflower.

2. The method for preparing a screen-printed electrode modified with layered bismuth nanoflowers according to claim 1, characterized in that, In step a, the bismuth salt is bismuth nitrate pentahydrate.

3. The method for preparing a screen-printed electrode modified with layered bismuth nanoflowers according to claim 1, characterized in that, In step a, the complexing agent is ethylenediaminetetraacetic acid, and the molar ratio of bismuth salt to complexing agent is 1:1.5-2.

5.

4. The method for preparing a screen-printed electrode modified with layered bismuth nanoflowers according to claim 1, characterized in that, In step a, the pH is adjusted to 3.0-4.0 by using NaOH and HCl or HNO3.

5. The method for preparing a screen-printed electrode modified with layered bismuth nanoflowers according to claim 1, characterized in that, In step b, the electrodeposition potential is from -1.1 V to -0.7 V; The deposition time is 60~360 s; the stirring speed during the deposition process is 200~300 rpm.

6. A screen-printed electrode modified with layered bismuth nanoflowers, obtained by any one of the preparation methods described in claims 1-5, characterized in that, The layered bismuth nanoflowers are composed of bismuth and have a two-dimensional hierarchical nanoflower structure formed by stacking layers of nanounits.

7. The application of the screen-printed electrode modified with layered bismuth nanoflowers as described in claim 6 in an electrochemical sensor.

8. The application of the screen-printed electrode modified with layered bismuth nanoflowers according to claim 7, characterized in that, The electrochemical sensor further includes a working electrode, a reference electrode, and a counter electrode. The working electrode is a layered bismuth nanoflower composite electrode; the reference electrode is Ag / AgCl; and the counter electrode is a graphite-carbon black composite conductive carbon electrode. The working electrode, reference electrode, and counter electrode are integrated on the same screen-printed electrode substrate.

9. The application of the screen-printed electrode modified with layered bismuth nanoflowers according to claim 8, characterized in that, The electrochemical sensor was applied to the square wave anodic stripping voltammetry method for the detection of Cd in water samples. 2+ and Pb 2+ This includes the following steps: a. Mix the water sample to be tested with the buffer solution and adjust the pH; b. Stirring at the enrichment potential; c. Square wave anodic stripping voltammetry was used to scan and record the stripping peak currents of cadmium and lead ions; d. Calculate Cd based on the dissolution peak currents of cadmium and lead ions obtained in step c. 2+ and Pb 2+ The concentration.

10. The application of the screen-printed electrode modified with layered bismuth nanoflowers according to claim 9, characterized in that, In step a, the buffer solution is an acetic acid and sodium acetate buffer solution with a concentration of 0.01-0.2 mol / L. The pH is adjusted to 3.5-5.5 by adding acetic acid and anhydrous sodium acetate. In step b, Pb 2+ The enrichment potential is -1.7 V to -1.1 V; Cd 2+ The enrichment potential ranges from -1.5 V to -1.1 V; the enrichment time ranges from 60 to 420 s. In step c, the potential step of the square wave anodic stripping voltammetry is 3-5 mV, the square wave amplitude is 20-30 Hz, and the frequency is 10-20 Hz.

Citation Information

Patent Citations

  • Preparation method and sensing application of bismuth nanoflower modified electrode

    CN115182012A

  • Preparation method and application of Cu-Bi / TiO2 nano electro-catalytic denitrification electrode

    CN115504544A